Neutron-induced effects on a self-refresh DRAM. (January 2022) - Matana Luza, Lucas; Söderström, Daniel; Puchner, Helmut; Alía, Rubén García; Letiche, Manon; Cazzaniga, Carlo; Bosio, Alberto; Dilillo, Luigi
Abstract: The field of radiation effects in electronics research includes unknowns for every new device, node size, and technical development. In this study, static and dynamic test methods were used to define the response of a self-refresh DRAM under neutron irradiation. The neutron-induced effects were investigated and characterised by event cross sections, soft-error rate, and bitmaps evaluations, leading to an identification of permanent and temporary stuck cells, single-bit upsets, and block errors. Block errors were identified in different patterns with dependency in the addressing order, leading to up to two thousand faulty words per event, representing a real threat from a user perspective, especially in critical applications. An analysis of the damaged cells' retention time was performed, showing a difference in the efficiency of the self-refresh mechanism and a read operation. Also, a correlation of the fault mechanism that generates both single-bit upsets and stuck bits is proposed. Post-irradiation high-temperature annealing procedures were applied, showing a recovery behaviour on the damaged cells. Highlights: Presented thermal & atmospheric-like neutrons induced effects on a self-refresh DRAM Presented a difference between the self-refresh mechanism and the read operation Uncovered correlation of the fault mechanism that generates both SBUs and stuck bits Presented a high-temperature annealing in radiation-induced faulty memory cells